Arts education in Ireland: Visions of a performative teaching, learning and research culture - Piazzoli, Erika (My University, 2023)
In this paper we offer an overview of the arts in education in Ireland, making a case for a performative approach. We dis- cuss theory, research and practice – situating the developments in Ireland within a multicultural context. We begin by offering our own definition of Arts (in) Education research, drawing on seminal policies and interrogating various art classifications, from a historical and etymological perspective. Next, we consider their impact at a global and regional level and we examine how policy has influenced the curriculum. Following this, we reflect on the ramifications of theatre and drama in education, highlighting the fragmentation in the field. In the main argument of the paper, we make a case for performative education, illustrating our vision for performative language teaching and research. We suggest that theory of aesthetic experience can be a useful framework, and close with remarks on our contemporary society.
PUBLISHED
Keywords: Performative language teaching; Arts (in) education; Aesthetic experience; Creative Arts Practice; Identities in Transformation; Arts Education; Drama and theatre in education; Drama education and language learning; Performative Language Teaching; Education